Investigations of the impact of initial stresses on fracture and delamination risks of an avionics MEMS pressure sensor. (August 2018) - Auersperg, J.; Auerswald, E.; Collet, C.; Dean, Th.; Vogel, D.; Winkler, Th.; Rzepka, S.
Abstract: Silicon based pressure sensors often take advantage of piezo-resistive gages which are normally embedded by multiple silicon oxide and silicon nitride layers where gold lines form a Wheatstone bridge (Meti et al., 2016; Bae et al., 2004 [2 ]). Because of manufacturing – stepwise deposition of multiple layers – significant layer residual stresses occur in the GPa range in tension and compression (Zhou et al., 2017 [3 ]). But also anodic bonding of the silicon MEMS device on usually glassy substrates results in additional initial stresses (Chou et al., 2009 [4 ] and Sandvan et al. [5 ]). Especially in avionics MEMS applications such stresses by far exceed the stresses arising under sensor operation and determine the major risks for cracking and delamination. Furthermore, those stresses could lead to a signal drift of the overall sensor over a long period of time — another important trustworthiness risk (Espinosa and Prorok, 2003 [6 ]). Highlights: Reliability issues concerning initial stresses in gage layer stacks of an avionics pressure sensor Interface fracture mechanics is utilized within a FEM framework — cohesive damage propagation simulation. Initial layer stresses from layer deposition processes taken from experiments X-FEM simulations carried out helped finding and explaining silicon cracking risks. Influence of temperature dependent thermal expansion behavior of several (glassy) substrates after wafer bonding